2017
DOI: 10.1002/slct.201702390
|View full text |Cite
|
Sign up to set email alerts
|

Ru(II)‐p‐cymene Thiosemicarbazone Complexes as Inhibitors of Amyloid β (Aβ) Peptide Aggregation and Aβ‐Induced Cytotoxicity

Abstract: The reaction of [RuCl2(η6‐p‐cymene)]2 with indole based thiosemicarbazone ligands (L1‐L3) yielded monometallic ruthenium(II) complexes, [RuCl(η6‐p‐cymene)(L)]Cl (1–3). The complexes were characterized by analytical and various spectroscopic (UV‐visible, FT‐IR, 1H & 13C NMR and mass) tools. The solid state structure of complex 2 determined by single crystal X‐ray diffraction analysis showed a piano stool geometry around the metal. The Ru(II)‐p‐cymene complexes with N‐substituted thiosemicarbazone were evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 69 publications
0
24
0
Order By: Relevance
“…To understand the effect of Fc moiety in catalysis, previously reported Ru(II)-pcymene complex containing indole TSC was employed as catalyst in the same reaction. [50] To our surprise, moderate activity i. e. 51 % selectivity of 3 a was observed compared to the present Fc-TSC complexes, inferring the synergistic effect between the Fc and Ru(II)-arene moieties.…”
Section: Synthesis Of 12-disubstituted Benzimidazolesmentioning
confidence: 47%
See 1 more Smart Citation
“…To understand the effect of Fc moiety in catalysis, previously reported Ru(II)-pcymene complex containing indole TSC was employed as catalyst in the same reaction. [50] To our surprise, moderate activity i. e. 51 % selectivity of 3 a was observed compared to the present Fc-TSC complexes, inferring the synergistic effect between the Fc and Ru(II)-arene moieties.…”
Section: Synthesis Of 12-disubstituted Benzimidazolesmentioning
confidence: 47%
“…Then, the arene moiety was changed from p ‐cymene to benzene ( 5 ); Ru(II) complex with the former arene unit displayed better activity over its benzene counterpart (Figure 4). To understand the effect of Fc moiety in catalysis, previously reported Ru(II)‐ p ‐cymene complex containing indole TSC was employed as catalyst in the same reaction [50] . To our surprise, moderate activity i. e .…”
Section: Resultsmentioning
confidence: 80%
“…Numerous biologically active molecules derived from natural sources contain a chromone moiety as their core. These compounds have attracted the pharmaceutical industries to a large extent owing to their antioxidant, antitumor and antibacterial activities. Besides these, several chromone derivatives have been used as antimicrobial, DNA-binding, DNA-cleavage, anticancer, antiallergic, neuroprotective, and pesticidal agents. Although the appeal of chromones and their derivatives is widespread, the literature still lacks knowledge about their importance in coordination chemistry. Our group has been meticulously involved in studying the coordination behavior of heterocyclic TSCs with Ni­(II), Cu­(II), Zn­(II), Pd­(II), and Ru­(II) and its influence on the biomolecular interactions and anticancer activity against various cancer and normal cell lines. Most of these complexes induced cell death through apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the complexes exhibited attenuation of Aβ induced cytotoxicity due to flexible alkyl substitution at terminal nitrogen of thiosemicarbazone moiety. [22] The anticancer activity of arene ruthenium complexes (Figure 2b) comprising (N,O)-attached ketoamine ligands with elevated IC 50 concentrations and a longer incubation period has been reported by Dyson et al In addition, the compounds displayed a stronger antivascular effect in the in vivo chicken chorioallantoic membrane model than RAPTA-C [23] Pettinari et al synthesized Ru (II)-areneacylpyrazolonato complexes (Figure 2c) and investigated their cytotoxicity with various cancer cells (MCF-7, HepG2, HeLa and HCT-116) with high IC 50 concentration. [24] Castonguay et al documented the anticancer activity of arene ruthenium complexes (Figure 2d) containing (N,O)-chelating Schiff base ligands on various cancerous and non-cancerous cells and demonstrated that ligand modification alters the biological activity of metal complexes.…”
Section: Introductionmentioning
confidence: 99%